Expanding the design space of gel materials through ionic liquid mediated mechanical and structural tuneability. Issue 3 (25th November 2019) - Brogan, Alex P. S.; Clarke, Coby J.; Charalambidou, Artemis; Loynachan, Colleen N.; Norman, Sarah E.; Doutch, James; Hallett, Jason P.
Abstract : The mechanical strength of ionogels correlates with polymer structure, which is dependent on the basicity of the ionic liquid anion. Abstract : Ionogels are an emerging class of soft material with exceptional properties stemming from high ionic liquid content. In contrast to other gel systems, the ionic liquid component provides an extra level of design. However, this highly modular nature has yet to be fully explored and the role ionic liquids play in the structural properties of gel-based materials is poorly understood. Here, methodical small angle neutron scattering and X-ray photoelectron spectroscopy studies reveal the relationship between bulk structure and surface composition of a soft material for the first time. Furthermore, we show how ionic liquid design dictates polymer structure, which in turn can be harnessed to fine tune the mechanical properties of ionogels. With a level of control over gel structure beyond what is possible using molecular solvents, our systematic study thus provides insight into how ionic liquids can expand the design space for gel development for a broad range of applications.